2024
DOI: 10.1039/d3nr06102g
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the potential: integrating nano-delivery systems with traditional Chinese medicine

Jianhua Zou,
Meng Li,
Ziwei Liu
et al.

Abstract: This review explores the potential of integrating nano-delivery systems with traditional Chinese herbal medicine, acupuncture, and Chinese medical theory. It highlights the intersections and potential of nano-delivery systems in enhancing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 128 publications
(154 reference statements)
0
1
0
Order By: Relevance
“…Currently, cinobufacini capsules and tablets in clinical use are administered orally, but this method is limited by poor water solubility, low permeability, instability, rapid metabolic elimination in the intestine and liver. 168 Cinobufacini and TV injections can overcome the limitations of oral administration via intramuscular or intravenous injection, but they exhibit rapid blood clearance, toxic side effects at high concentrations, and weak tumor targeting, resulting in suboptimal effects. Numerous studies have demonstrated that TS/TV and active ingredients of TDDS were designed by intravenous administration delivery, which allowed them to improve water solubility, enhance stability, prolong blood circulation time, reduce internal clearance, and have good tumor targeting, thereby enhancing their therapeutic efficacy.…”
Section: Conclusion and Prospectivesmentioning
confidence: 99%
“…Currently, cinobufacini capsules and tablets in clinical use are administered orally, but this method is limited by poor water solubility, low permeability, instability, rapid metabolic elimination in the intestine and liver. 168 Cinobufacini and TV injections can overcome the limitations of oral administration via intramuscular or intravenous injection, but they exhibit rapid blood clearance, toxic side effects at high concentrations, and weak tumor targeting, resulting in suboptimal effects. Numerous studies have demonstrated that TS/TV and active ingredients of TDDS were designed by intravenous administration delivery, which allowed them to improve water solubility, enhance stability, prolong blood circulation time, reduce internal clearance, and have good tumor targeting, thereby enhancing their therapeutic efficacy.…”
Section: Conclusion and Prospectivesmentioning
confidence: 99%